2020
DOI: 10.3390/molecules25122816
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Evaluation of Novel bis(2-aminoethyl)amine Derivatives

Abstract: Seven novel derivatives of bis(2-aminoethyl)amine were synthesized. For compounds 1 and 7 single crystals were isolated and X-ray diffraction experiments were done. Lipophilicity and drug likeness were calculated in the initial stage of research. All compounds were screened for their in vitro cytotoxic activity against a panel of human cancer cell lines, which is contrary to normal (HaCaT) cell lines, by using the MTT method. Studies were followed by lactate dehydrogenase assay, apoptotic activity, and interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The main goal in the current design was to replace the thiourea arrangement with a tetrazole scaffold. Twelve new N -(furan-2-ylmethyl)-1 H -tetrazol-5-amine derivatives were synthesized according to the well-known procedure [ 15 ]. Reaction conditions are depicted below ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main goal in the current design was to replace the thiourea arrangement with a tetrazole scaffold. Twelve new N -(furan-2-ylmethyl)-1 H -tetrazol-5-amine derivatives were synthesized according to the well-known procedure [ 15 ]. Reaction conditions are depicted below ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description related to all conducted biological studies including cell culture, suitable conditions, and methodology was presented in our previous papers [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous years, our research group was devoted to searching for new tetrazole-based compounds with antimicrobial activity [ 22 , 23 , 24 , 25 ]. Clinicians use the tetrazole-derived antimicrobial drugs such as Cefamandole, Ceftezole, both second-generation broad-spectrum cephalosporin antibiotics, and the oxazolidinone-class antibiotic Tadalizolid.…”
Section: Introductionmentioning
confidence: 99%
“…Thiourea derivatives of two imides with confirmed antimicrobial activity were used as substrates for the synthesis of tetrazole-imide hybrids [ 29 , 30 ]. Our previous studies showed that the introduction of tetrazole arrangement in thiourea derivatives leads to an increase of antimicrobial activity [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%